2020
DOI: 10.1111/jcmm.15548
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ER stress signalling increases mortality after a major trauma

Abstract: The endoplasmic reticulum (ER) adapts to stress by activating a signalling cascade known as the ER stress response. While ER stress signalling is a central component of the cellular defence against environmental insult, persistent activation is thought to contribute to the progression of various metabolic complications via loss of protein function and cell death. Despite its importance however, whether and how ER stress impacts morbidity and mortality in conditions of hypermetabolism remain unclear. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…Burn patients suffer from a chronic increase in β-adrenergic signaling mediated by catecholamines, known inducers of endoplasmic reticulum stress and lipolysis. 15 While the initial spike in epinephrine and norepinephrine levels is of benefit to fuel the fight-or-flight response, the perpetual stimulation of lipolysis induces an extreme loss of WAT mass that is only partially mitigated by β-blockade. 16 To that effect, we have turned our attention toward the study of lipolytic enzymes as effectors of poor outcomes post-burn and the possibility of therapeutically targeting lipolysis in hypermetabolism to limit FFA-mediated damage to lean muscle and internal organs.…”
Section: Introductionmentioning
confidence: 99%
“…Burn patients suffer from a chronic increase in β-adrenergic signaling mediated by catecholamines, known inducers of endoplasmic reticulum stress and lipolysis. 15 While the initial spike in epinephrine and norepinephrine levels is of benefit to fuel the fight-or-flight response, the perpetual stimulation of lipolysis induces an extreme loss of WAT mass that is only partially mitigated by β-blockade. 16 To that effect, we have turned our attention toward the study of lipolytic enzymes as effectors of poor outcomes post-burn and the possibility of therapeutically targeting lipolysis in hypermetabolism to limit FFA-mediated damage to lean muscle and internal organs.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these findings, anti‐IL‐6‐treated mice were also protected from burn‐induced hepatic steatosis as their livers showed reductions in both fat infiltration and TG content relative to untreated burned mice. We and others have previously shown that fat infiltration in the liver if left unabated can induce ER stress mediated hepatic apoptosis and damage 28 . Remarkably, anti‐IL‐6‐treated burned mice also showed reductions in key markers of ER stress and liver damage, suggesting that the beneficial effects of anti‐IL‐6 mAb were not limited to just inhibiting lipid infiltration.…”
Section: Discussionmentioning
confidence: 79%
“…We and others have previously shown that fat infiltration in the liver if left unabated can induce ER stress mediated hepatic apoptosis and damage. 28 Remarkably, anti-IL-6-treated burned mice also showed reductions in key markers of ER stress and liver damage, suggesting that the beneficial effects of anti-IL-6 mAb were not limited to just inhibiting lipid infiltration. These hepatic findings regarding IL-6 blockade might seem contradictory in the context of studies that have associated IL-6 signaling in accelerating liver regeneration.…”
Section: F I G U R Ementioning
confidence: 97%
“…ER is a dynamic organelle which can quickly adapt in order to satisfy various cellular requirements in response to physiological or pathological stimuli [3]. The ER adapts to stress by activating a signaling cascade known as the ER stress response [4]. As guardians of the ER, a three-branch system composed by three transmembrane proteins will be activated during ER stress response.…”
Section: Introductionmentioning
confidence: 99%